2020
DOI: 10.1073/pnas.1921315117
|View full text |Cite
|
Sign up to set email alerts
|

Necroptosis-based CRISPR knockout screen reveals Neuropilin-1 as a critical host factor for early stages of murine cytomegalovirus infection

Abstract: Herpesviruses are ubiquitous human pathogens that cause a wide range of health complications. Currently, there is an incomplete understanding of cellular factors that contribute to herpesvirus infection. Here, we report an antiviral necroptosis-based genetic screen to identify novel host cell factors required for infection with the β-herpesvirus murine cytomegalovirus (MCMV). Our genome-wide CRISPR-based screen harnessed the capacity of herpesvirus mutants that trigger antiviral necroptotic cell death upon ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 59 publications
4
29
0
Order By: Relevance
“…Then, the virion pellets were purified using anti-CD44 microbeads and a magnetic-based method and subsequently analyzed using liquid chromatography and mass spectrometry (MS) to identify the cellular proteins incorporated into the virions. NRP-1, originally identified as a neuronal and endothelial cell receptor required for embryonic development, axon guidance, and vasculature formation ( 15 17 ), was found in HIV-1 particles produced from macrophages and not from CD4 + T cells ( SI Appendix , Table S1 ) ( 9 14 ). To validate NRP-1’s incorporation into viral particles, we infected primary MDMs with or without HIV-1 ( SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the virion pellets were purified using anti-CD44 microbeads and a magnetic-based method and subsequently analyzed using liquid chromatography and mass spectrometry (MS) to identify the cellular proteins incorporated into the virions. NRP-1, originally identified as a neuronal and endothelial cell receptor required for embryonic development, axon guidance, and vasculature formation ( 15 17 ), was found in HIV-1 particles produced from macrophages and not from CD4 + T cells ( SI Appendix , Table S1 ) ( 9 14 ). To validate NRP-1’s incorporation into viral particles, we infected primary MDMs with or without HIV-1 ( SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We conducted experiments to identify and compare the cellular protein produced by macrophages and activated CD4 + T lymphocytes that were incorporated into virions. As a result, we uncovered a transmembrane protein, neuropilin-1 (NRP-1) ( 9 14 ), that was only present in the virions produced in macrophages but not CD4 + T cells. Here, we report that the gene encoding NRP-1, a newly identified antiviral factor, is highly expressed in macrophages and DCs.…”
mentioning
confidence: 99%
“…It has been observed that the proportion of individuals infected with CMV increases with age, similarly to the mortality rate of SARS-CoV-2 which also increases with age, and that CMV infection is linked to immune dysfunction, inter alia, the chronic activation of T cells. Therefore, it has been suggested that CMV infection is a negative risk factor for patient's clinical status following SARS-CoV-2 infection [41][42][43][44].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, some endogenous substrates of furin, such as class 3 semaphorins, bind to NRPs as their cell surface coreceptors ( 30 32 ). Seven viruses to date have been shown to use NRPs as cellular (co-)receptors: the coronavirus SARS-CoV-2 ( 33 , 34 ), retroviruses human T cell lymphotropic virus-1 (HTLV-1) and HTLV-2 ( 35 , 36 ), the herpesviruses Epstein-Barr virus (EBV) ( 37 , 38 ), mouse cytomegalovirus (mCMV) ( 39 ), human cytomegalovirus (hCMV) ( 40 ), and the arenavirus Lujo virus (LUJV) ( 41 , 42 ) ( Table 1 ). The spike glycoproteins of all these viruses contain polybasic sites that are cleaved or can potentially be cleaved by a PC.…”
Section: Nrps As Viral Entry Factorsmentioning
confidence: 99%